Significance of near-wall dynamics in enhancement of heat flux for roughness aided turbulent Rayleigh–Bénard convection - Chand, Krishan; Sharma, Mukesh; De, Arnab Kr (Physics of fluids (1994), 2021)
We report a numerical investigation of the effect of multiscale roughness on heat flux ( N u ) and near-wall dynamics in turbulent Rayleigh–Bénard convection of air in a cell of aspect ratio 2 in the Rayleigh number ( R a ) range 10 6 ≤ R a ≤ 4.64 × 10 9. We observe that despite the same wetted area, taller roughness yields higher heat flux owing to a multiple roll state. Based on the number of roughness peaks penetrating the thermal boundary layer, three regimes are identified. In regime I, heat flux drops marginally as only 50% of the peaks emerge uncovered, followed by a nearly unaltered Nu in regime II. A sudden increase in Nu in regime III is noted with more than 65% penetrating peaks. In contrast to the previous observation, heat flux continues to increase even when all the peaks exceed the boundary layer. Transformation of two large-scale rolls into smaller multiple rolls favors better access to the trapped fluid in the roughness throat leading to greater mixing. A significant improvement in the mixing of fluid inside the cavities is found due to the cascade of secondary vortices, which is connected to the improved heat flux in the tallest roughness setup. A thin thermal boundary layer that envelopes the rough surface at higher Ra supports the enhanced inter-mixing of fluid inside the cavities. Greater perturbation of the thermal boundary layer for the smaller roughness setup shows consistent connection with the enhanced N u ( R a ) scaling.